Tytuł profesora w Polsce w latach 1920–1990. Część 2. Warunki nadawania tytułu profesora w prawie o stopniach i tytułach naukowych - Wojtczak, Krystyna (Studia Prawa Publicznego, 2018)
The issues concerning the conferment of the title of Professor regulated by the law on academic degrees and academic titles covered a period of twenty-five years. This is much shorter than subjecting proceedings in this area to the law on higher education for the past forty-five years. It is not without reason that during the seventy years (1920–1990) covered by both parts of the study issues related to the conferring the title of professor were subject to significant changes, in accordance with the changing legal and factual reality of the People’s Republic, the Polish People’s Republic, and the Republic of Poland. The 1965 Act on Academic Degrees and Scientific Titles undoubtedly differed from the legislation in force in the People’s Republic and in the first years of the Polish People’s Republic. Its unquestioned advantage was: (1) a limited number of academic titles of professor, restricted to extraordinary and ordinary professor, (2) identified fields of science in which these titles could be awarded, and (3) a gradual simplification of the procedure for applying for the award of the academic title to a candidate in universities, scientific institutions of the Polish Academy of Sciences and research institutes. Although in this respect, the provisions of the Act of 1965 together with the secondary legislation issued on its basis were subject to amendments, as a rule they were limited to clarifying the legal solutions adopted earlier, or to increasing the requirements imposed on candidates for the title of professor, except for candidates not possessing a degree or a scientific title, subject to a separate legal regime dictated by exceptional cases. The wider scope of changes concerned the procedure for presenting to the Prime Minister by competent ministers and the Scientific Secretariat of the Polish Academy of Sciences (PAN) candidates for the academic title and the requirements related to the obligation put on these bodies to seek the opinion of the General Council for Higher Education, the Central Qualification Commission, or competent Higher Education Councils in the scope of a relevant science.